A Theoretical Artificial Intelligence Framework for Electricity Generation Life Cycle - Mnkandla, Ernest (The Indonesian Journal of Computer Science, 2022)
The global economic growth heavily lies on the manufacturing sector. However, over the past decade, manufacturing sector in general has been facing a serious production downturn, hence, operating below its capacity mostly due to its inefficient and ineffective production system. Additionally, due to failure for manufacturing sector to constantly measure, develop and implement novel approaches in order to make sure it positions itself for economic growth as well as unlocking new opportunities within the ever-changing and complex worldwide market environment. However, ss of 2011, Industrial revolution 4.0 seems to have been a crucial factor in reshaping the sociological, economic, and technological landscape. Businesses associated with exposure to continuous digital transformation are able to capitalize on Industrial revolution 4.0 potential but are also compelled to deal with various impediments. Yet, research on the opportunities associated with the integration of Industry 4.0 in manufacturing industries from a holistic perspective is scarce. To fill this research gap, this study adopted the PRISMA approach to conduct a thorough investigation on the potential opportunities related to the adoption of industry 4.0 in the context of manufacturing businesses.